The silence of race: contextures of racism and Social Workers in Belém (PA) - Nascimento, Maria Antonia Cardoso; Castilho, Daniela Ribeiro; Campos, Suzani Tavares (Argumentum, 2024)
This article analyses how racism has been seen by social workers in Belém (PA). To do so, it provides a brief contextualisation of the ethnic-racial issue in regional literature, presenting insights on the ethnic-racial debate in Brazilian Social Work, its relationship with components of the curriculum and the profile of social workers, based on race/ethnicity, gender, age, place of residence, professional practice, salary, and religion. Then, through the analysis of an applied questionnaire, it examines the silencing of social workers regarding their professional experience of racism and verifies that the majority of respondents have difficulty discussing the implications of racism in general and within social work practice, behaviour that reveals the subjectivity shaped by whiteness and the limitations of professional training regarding this issue.